PENGARUH KECEPATAN LAYANAN DAN KERAMAHAN LAYANAN TERHADAP KEPUASAN PELANGGAN DIRUMAH KOPI LAMONGAN - Moh Azus shony Azar; Achmad Efendi (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
: This research to analyze the effect of service speed and service friendliness on the satisfaction of Lamongan coffee house customers. The sample in this study were 100 respondents. Data collection method in this study is questionnaire and documentation study. The method of data analysis uses descriptive quantitative methods, namely with multiple linear regression analysis and classical assumption tests.Based on the F test results obtained F-count is greater than F-count 204.254> F table value = 3.09, service speed and service friendliness together have a positive effect on customer satisfaction. Based on the T Test Service speed (X1) has a positive and significant effect on customer satisfaction, Service friendliness (X2) has a positive and significant impact on customer satisfaction. Service speed is the most influential variable on customer satisfaction. Through testing the Determination Coefficient by adjusted R Square (R2) 80.4%, customer satisfaction can be explained by variable service speed and service friendliness, while 19.6% performance can be explained by other variables not examined by this study.